Thermal Deformation and Strength of Materials for Heat-shielding Coatings of a Spacecraft on the Trajectory of Descent from Orbit - Gracheva, Lyudmila I. (Techniques and Innovation in Engineering Research Vol. 2, 2022)
The concordance between experimental research and the real operating circumstances of a given model or structure forms the basis of a fundamental understanding of the mechanism of material interaction with a medium. Design of Thermal Shield Materials (TSMs) is based on some criteria such as parameters of heating and destruction of materials under minimal weight of the shield. The less its weight, the more useful space load it can deliver. Thermal shield is a ballast weight for a missile, therefore it is natural to desire to reduce the weight of TSMs without reliability loss of its thermal shield function. The performance of thermal shield structures was investigated using computations based on physical properties of materials obtained under conditions simulating a spacecraft's re-entry into the atmosphere. Physical modeling of natural conditions of thermal shield use (temperature, heating/cooling rate, composition, and pressure of gas medium) is based on the dependence of temperature T of a side surface of thermal shield on the time of descent in dense atmospheric layers. A layered fibreglass shell with a phenol-phormaldehyde matrix made up a thermal barrier. Temperature-dependent mechanical and thermophysical properties were investigated. It is possible to characterise the thermally stressed state of a cylindrical shield that is being affected by a high-temperature gas flow by simultaneously applying numerical analysis, elasticity theory, and thermal conductivity equations to solve a 3D problem. The findings demonstrated that the largest compression stresses in a fibreglass thermal shield shell are concentrated near the heated surface and are not greater than the material's strength limit at that temperature. The studies carried out were of practical importance: on the basis of the experimental and theoretical studies carried out, a new, 30% lighter, thermal protection system for the re-entry vehicle was proposed and implemented.